Multifaceted Therapeutic Potential of Plant-Derived Exosomes: Immunomodulation, Anticancer, Anti-Aging, Anti-Melanogenesis, Detoxification, and Drug Delivery - Arzu Zeynep Karabay; Jaleh Barar; Yalda Hekmatshoar; Yalda Rahbar Saadat (Biomolecules)
Most eukaryotic and prokaryotic cells have the potential to secrete a group of structures/membrane-bound organelles, collectively referred to as extracellular vesicles (EVs), which offer several advantages to producer/receiver cells. This review provides an overview of EVs from plant sources with emphasis on their health-promoting potential and possible use as therapeutic agents. This review highlights the essential biological effects of plant-derived extracellular vesicles, including immune modulation, anticancer activities, protection against chemical toxicity and pathogens, as well as anti-aging, anti-melanogenesis, and anti-arthritic effects, along with ongoing clinical studies. Evidence revealed that plant-derived EVs’ contents exert their beneficial properties through regulating important signaling pathways by transferring miRNAs and other components. Taken all together, the data proposed that plant-derived EVs can be utilized as nutritional compounds and therapeutic agents, such as drug carriers. However, this emerging research area requires further in vitro/in vivo studies and clinical trials to determine the exact underlying mechanisms of EVs’ positive health effects in treating various diseases.